Samuel Whittemore Boggs papers - Boggs, Samuel Whittemore, 1889-1954.
Correspondence, speeches, writings, subject files, research data, printed matter, maps, and other papers relating mainly to Boggs's geographic studies and to his inventions and research interests. Includes files of geographic data on various regions of the world, reports of missionary activity, and material relating to Boggs's pioneering work as inventor of an eumorphic equal-area map projection, graphic traffic signals, and a universal graphic charting instrument. Subjects include boundary delimitation, water boundaries, regionalism, and global relations.
Geographer, inventor, and cartographer.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Boundaries; Cartography; Cartography -- Instruments; Geography; International relations; Map projection; Maps; Missions; Regionalism; Traffic signs and signals; Water boundaries; Authors; Cartographers; Geographers; Inventors